Genetic resources for plantation forestry - Boyle, T.J.B.; Cossalter, C.; Grifin, A.R. (1997)
Relatively few tropical species have been used extensively in plantations. Species of pines and eucalypts are used in about one-third of the total area of tropical forest plantations, and acacias are also commonly planted. In utilising genetic resources effectively, it is important to assess the relative contributions of the genotype and the environment to the phenotype, and the relative magnitude of genetic variation at each level in the genetic hierarchy: species, provenances, and down to individual trees. The significance of quantitative variation and molecular genetics in the selection of genetic resources is discussed and the use of these different types of information in the design and implementation of tree improvement strategies described. Diff erent approaches to the selection of genetic resources at each level of the genetic hierarchy are reviewed with particular reference to selection for water and nutrient use efficiency. While marker-aided selection, physiological testing and modelling may be valuable in the future, traditional field testing remains an absolute necessity.